Linagliptin for Type 2 Diabetes Mellitus: A Systematic Review of Efficacy, Safety, Combination Therapy, and Use in High Risk Populations - Nazwa Rizkillah; Keysha Feiruzyan Rafeufadattis; Nandita Aulia; Verka Apriani; Hadi Sudarjat (Healthy Tadulako Journal (Jurnal Kesehatan Tadulako), 2026)
Background: Type 2 diabetes mellitus requires glucose-lowering therapy that balances efficacy and safety, particularly in patients with renal or cardiovascular comorbidities. Linagliptin is a dipeptidyl peptidase-4 inhibitor with predominantly nonrenal elimination. Objectives: To evaluate the efficacy, safety, combination therapy, and clinical use of linagliptin in selected high-risk populations. Methods: PubMed and Google Scholar were searched for primary clinical studies published from 2015 through 19 August 2026. Eleven eligible studies were synthesized according to PRISMA 2020 principles. Risk of bias was assessed using RoB 2, and clinically heterogeneous outcomes were summarized narratively. Results: Linagliptin reduced HbA1c compared with placebo and demonstrated cardiovascular noninferiority in CARMELINA. Compared with glimepiride, glycemic control was broadly comparable, with less hypoglycemia and weight gain. Empagliflozin produced greater glycemic and metabolic improvements than linagliptin when added to premixed insulin, whereas linagliptin reduced HbA1c more effectively than voglibose in hemodialysis patients. Combination benefits and adverse effects varied according to the partner drug. Conclusions: Linagliptin provides modest glucose lowering with a generally low risk of hypoglycemia, although comparative benefits depend on population, comparator, and clinical outcome.